2002
DOI: 10.1177/0306624x02461007
|View full text |Cite
|
Sign up to set email alerts
|

Inmate Family Functioning

Abstract: Two-hundred-nine noninmates and 169 inmates completed questionnaires that assessed retrospective perceptions of 12 dimensions of family life and one overall assessment of quality of family life. Between the inmates and noninmates, means for all dependent variables differed significantly except for self-reliance; however, meaningful eta-squares were found only for dimensions of bridging, disengagement, and quality of life. Among the independent-samples t tests for gender, eta-squares were not meaningful. Implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 19 publications
(38 reference statements)
1
16
0
Order By: Relevance
“…However, the authors reported many incarcerated fathers were open to interventions to address those limitations and to improve the lives of their children. The findings are congruent with prior research on inmates showing they often realize their family relationships prior to incarceration were imperfect and they welcomed the opportunity while in prison to address and improve those relationships (Carlson & Cervera, 1991;Klein et al, 2002). Hairston's (2007) more recent study found family ties had positive effects on the postrelease success of those male prisoners who consistently maintained family ties during incarceration and assumed familial responsibilities after release.…”
Section: Family Support and Incarcerated Fatherssupporting
confidence: 84%
See 3 more Smart Citations
“…However, the authors reported many incarcerated fathers were open to interventions to address those limitations and to improve the lives of their children. The findings are congruent with prior research on inmates showing they often realize their family relationships prior to incarceration were imperfect and they welcomed the opportunity while in prison to address and improve those relationships (Carlson & Cervera, 1991;Klein et al, 2002). Hairston's (2007) more recent study found family ties had positive effects on the postrelease success of those male prisoners who consistently maintained family ties during incarceration and assumed familial responsibilities after release.…”
Section: Family Support and Incarcerated Fatherssupporting
confidence: 84%
“…Most of the men she surveyed (75%) reported high levels of closeness, contact, and involvement prior to incarceration. In contrast, in their study of inmate family functioning, Klein, Bartholomew, and Hibbert (2002) found inmates had high levels of disengagement and low cohesion among their family units. However, the authors reported many incarcerated fathers were open to interventions to address those limitations and to improve the lives of their children.…”
Section: Family Support and Incarcerated Fathersmentioning
confidence: 77%
See 2 more Smart Citations
“…For example, researchers have recently confirmed a strong relationship between family contact during incarceration and lower rates of recidivism (Bales & Mears, 2008;Hairston, 2002;Klein, Bartholomew, & Hibbert, 2002). Inmates visited more often and more recently had the lowest rates of recidivism in a large study of prison visitation in Florida (Bales & Mears, 2008).…”
Section: The Role Of Family In Prisoner Reentrymentioning
confidence: 99%